Spin field effect transistors and their applications: A survey. (December 2020) - Malik, Gul Faroz Ahmad; Kharadi, Mubashir Ahmad; Khanday, Farooq Ahmad; Parveen, Nusrat
Abstract: Among the various devices being researched as possible alternative for conventional scaled down transistor, the spin-FET (Datta-Das transistor) held some early promise. Various research groups have proposed the complementary spin-FETs viz., parallel and anti-parallel spin-FETs, later designed some basic and higher order logic circuits using them, and compared the performance with the conventional CMOS design. Various bulk materials like InAs, InAlAs etc. and 2D materials like graphene, silicene etc. have been used as channel materials in spin-FETs by many researchers. Different ferromagnetic and half-metallic electrodes like cobalt, nickel, CrO2 have also been employed in the spin-FETs. Several research groups have worked on the usage of multi-gate and multifunctional logic using spin-FET devices. In this paper, a review of the development of spin-FETs and spin-FET based design has been performed. In addition, the various applications of spin-FETs and the challenges faced for the implementation of spin-FETs are highlighted in the paper.